Protective CD4+ Th1 cell-mediated immunity is reliant upon execution of effector function prior to the establishment of the pathogen niche. - Leah S Hohman (Public Library of Science (PLoS), 2021)
Intracellular infection with the parasite Leishmania major features a state of concomitant immunity in which CD4+ T helper 1 (Th1) cell-mediated immunity against reinfection coincides with a chronic but sub-clinical primary infection. In this setting, the rapidity of the Th1 response at a secondary site of challenge in the skin represents the best correlate of parasite elimination and has been associated with a reversal in Leishmania-mediated modulation of monocytic host cells. Remarkably, the degree to which Th1 cells are absolutely reliant upon the time at which they interact with infected monocytes to mediate their protective effect has not been defined. In the present work, we report that CXCR3-dependent recruitment of Ly6C+ Th1 effector (Th1EFF) cells is indispensable for concomitant immunity and acute (<4 days post-infection) Th1EFF cell-phagocyte interactions are critical to prevent the establishment of a permissive pathogen niche, as evidenced by altered recruitment, gene expression and functional capacity of innate and adaptive immune cells at the site of secondary challenge. Surprisingly, provision of Th1EFF cells after establishment of the pathogen niche, even when Th1 cells were provided in large quantities, abrogated protection, Th1EFF cell accumulation and IFN-γ production, and iNOS production by inflammatory monocytes. These findings indicate that protective Th1 immunity is critically dependent on activation of permissive phagocytic host cells by preactivated Th1EFF cells at the time of infection.